Administrative execution, an Applied comparative analytical study in Light of Islamic Jurisprudence and the Enforcement System before the Board of Grievances System and its Implementing - Ahmed Abdulwahab Ahmed Ababtain (International Journal of Law Research and Studies, 2026)
The present study aims to identify the characteristics and historical development of Wilāyat al-Maẓālim (the jurisdiction of grievances) in Islamic history and jurisprudence, as well as its most important institutions and governing principles. It further seeks to compare this institution with the Saudi Board of Grievances (Dīwān al-Maẓālim) as an administrative judiciary under Saudi laws. To achieve these objectives, the researcher adopted the inductive analytical approach by examining and analyzing the implementation of Saudi regulations related to the enforcement of administrative judgments in the Kingdom of Saudi Arabia, as issued by the courts of the Board of Grievances, and comparing them with the practices established in Islamic jurisprudence. The study concludes that the judiciary of grievances emerged as a strong institution during the Islamic state, where it was exercised directly by the Caliph himself or by his governors holding general authority, due to the gravity and significance of its functions. This judiciary was entrusted with examining abuses committed by governors against subjects, disputes concerning workers’ wages, and other forms of grievances. The researcher also concludes that the Saudi Board of Grievances derives its foundations and rules from Islamic jurisprudence, particularly with regard to its subordination to the Ruler (Walī al-Amr) and its adherence to the principles of Islamic Sharia. At the same time, it adopts modern judicial mechanisms, such as the duality of the judiciary, the principle of litigation at two levels, and the separation between adjudicatory jurisdiction and enforcement jurisdiction. In light of these findings, the researcher recommends expanding the jurisdiction of enforcement within the Saudi grievance system in order to safeguard judicial rulings and ensure their effective implementation.